2020
DOI: 10.1111/1462-2920.15084
|View full text |Cite
|
Sign up to set email alerts
|

Role of enterotoxigenic Escherichia coli prophage in spreading antibiotic resistance in a porcine‐derived environment

Abstract: Enterotoxigenic Escherichia coli (ETEC) cause acute secretory diarrhoea in pigs, posing a great economic loss to the swine industry. This study analysed the prevalence and genetic characteristics of prophages from 132 ETEC isolates from symptomatic pigs to determine their potential for spreading antibiotic resistance. A total of 1105 potential prophages were identified, and the distribution of the genome size showed three 'overlapping' trends. Similarity matrix comparison showed that prophages correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Phage or prophage-carrying AMR genes are reported to be minor HGT agents ( 37 , 38 ). In recent years, however, several studies have reported that AMR genes are present in the phage or prophage region ( 39 42 ), implying that they are associated with the prophage region more than expected. Nevertheless, there have been few reports comprehensively identifying and analyzing AMR/VF genes located in the prophage region of nosocomial AMR pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…Phage or prophage-carrying AMR genes are reported to be minor HGT agents ( 37 , 38 ). In recent years, however, several studies have reported that AMR genes are present in the phage or prophage region ( 39 42 ), implying that they are associated with the prophage region more than expected. Nevertheless, there have been few reports comprehensively identifying and analyzing AMR/VF genes located in the prophage region of nosocomial AMR pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of ARGs in Lactobacillus is well known, and many strains show phenotypic multidrug resistance ( 48 ). Foodborne drug-resistant bacteria may promote the transfer of ARGs to other commensal microorganisms in the human gastrointestinal tract ( 49 ), thus posing a threat to public health and food safety ( 50 ), while a complete prophage is a crucial carrier and reservoir of ARGs ( 51 ), leading to the widespread dissemination of antibiotic resistance ( 52 ). Therefore, ubiquitous prophages should arouse our attention to assess the risk of antibiotic resistance transfer in Lactobacillus .…”
Section: Discussionmentioning
confidence: 99%
“…Phage or prophage-carrying AMR genes are reported to be minor HGT agents (34, 35). In recent years, however, several studies have reported that AMR genes are present in the phage or prophage region (3639), implying that they are associated with the prophage region more than expected. Nevertheless, there have been few reports comprehensively identifying and analyzing AMR/VF genes encoded in the prophage region of nosocomial AMR pathogens.…”
Section: Discussionmentioning
confidence: 95%